Efficient Navigation with Language Pre-training and Stochastic Sampling - li, xiujun; Li, Chunyuan; Xia, Qiaolin; Celikyilmaz, Asli; Gao, Jianfeng; Smith, Noah A.; Choi, Yejin (EMNLP-IJCNLP, 2019)
Efficient Navigation with Language Pre-training and Stochastic Sampling